Impact of Follicular Menstrual Phase on Body Composition Measures and Resting Metabolism. Issue 11 (November 2021) - GOULD, LACEY M.; CABRE, HANNAH E.; BREWER, GABRIELLE J.; HIRSCH, KATIE R.; BLUE, MALIA N. M.; SMITH-RYAN, ABBIE E.
ABSTRACT: Purpose: This study aimed to identify the effects of early follicular (EF) and midfollicular (MF) menstrual phases on body composition, resting metabolic rate (RMR), and respiratory quotient (RQ) assessment accuracy to identify an optimal testing period. Methods: Body composition was obtained from a four-compartment (4C) criterion model (fat mass (FM), fat-free mass, body fat percent, and dual-energy x-ray absorptiometry (DXA; FM, lean mass (LM), trunk FM, and trunk LM) in 19 eumenorrheic females (mean ± SD: age, 21.3 ± 3.1 yr, body mass index, 23.6 ± 1.8 kg·m −2 ). RMR (kcal·d −1 ) and RQ (a.u.) were measured via indirect calorimetry for 25 min. Body composition, RMR, and RQ were measured during the EF and MF phases. Dependent-samples t -tests were used to compare outcomes between EF and MF. Results: 4C outcomes were similar between phases ( P > 0.05). During EF, the following 4C components were significantly greater ( P < 0.05): body volume (mean difference (MD) ± SD, 0.70 ± 1.05 L), extracellular fluid (MD ± SD, 0.27 ± 0.51 L), and body mass (MD ± SD, 0.56 ± 0.80 kg). DXA-measured LM, body fat percent, trunk LM, and trunk FM were similar ( P > 0.05); however, DXA FM was significantly greater during EF (MD ± SD, 0.29 ± 0.40 kg; P = 0.005), yet within measurement error of the device. Although RMR was not significantly different between phases (MD ± SD, 6.0 ± 190.93 kcal·d −1 ; P > 0.05), RQ was significantly higher during EF (mean ± SD, 0.03 ± 0.06 a.u.; P = 0.029) compared with MF. Conclusions: Body composition from 4C and DXA do not seem to be affected beyond measurement error as a result of compartmental changes from the menstrual cycle. During MF, women oxidized more fat as demonstrated by a lower RQ. Researchers should aim to be more inclusive and schedule testing for females within 11–12 d from the onset of menstruation.